Pengembangan Bahan Ajar Cerita Rakyat Kepahiang “Asal Mula Lubuk Lebar” Berbasis Cergam pada Pembelajaran Bahasa Indonesia untuk Penguatan Literasi Peserta Didik Kelas IV SDN 09 Kepahiang - Nadia; Muktadir, Abdul; Parmadi, Bambang (UNIB Press, 2025)
The purpose of this study was to develop, describe the level of feasibility, find out the user's response and find out the effectiveness of the Development Of Kepahiang Folk Story Teaching Materials “Origins Of Lubuk Lebar” Based On Picture Stories In Indonesian Language Learning For Strengthening Literacy Of Class IV Students At SDN 09 Kepahiang. The type of research used is research and development (Research and development). The research model in the development of teaching materials is the ADDIE model. The type of data used is quantitative and qualitative data using instruments in the form of interviews, needs analysis questionnaires, questions, expert validation sheets and user response questionnaires. Based on the results of the study it can be concluded that the teaching materials that have been developed are suitable for use as teaching materials in class IV Indonesian content. The results of expert validation were 0.95 from material expert validation and 0.94 from design expert validation, and 0.96 from linguist validation. The user response was very good because the results of the class IV teacher questionnaire analysis showed a percentage of 95% with very good criteria. As for the response from students, it obtained a percentage of 95.4% with very good criteria. The teaching materials developed are effective for increasing the literacy literacy of fourth grade students at SD Negeri 09 Kepahiang. This is based on the results of obtaining an average value of 80.5 with a completeness presentation of 83%.